A secreted pore‐forming protein modulates cellular endolysosomes to augment antigen presentation. Issue 10 (12th August 2020) - Deng, Cheng‐Jie; Liu, Long; Liu, Ling‐Zhen; Wang, Qi‐Quan; Guo, Xiao‐Long; Lee, Wen‐Hui; Li, Sheng‐An; Zhang, Yun
Abstract: Bacterial pore‐forming toxin aerolysin‐like proteins are widely distributed in animals and plants. Emerging evidence supports their roles in host innate immunity, but their direct actions in adaptive immunity remain elusive. In this study, we found that βγ‐CAT, an aerolysin‐like protein and trefoil factor complex identified in the frog Bombina maxima, modulated several steps of endocytic pathways during dendritic cell antigen presentation. The protein augmented the antigen uptake of dendritic cells and actively neutralized the acidification of cellular endocytic organelles to favor antigen presentation. In addition, the release of functional exosome‐like extracellular vesicles was largely enhanced in the presence of βγ‐CAT. The cellular action of βγ‐CAT increased the number of major histocompatibility complex (MHC) I‐ovalbumin and MHC II molecules on dendritic cell surfaces and the released exosome‐like extracellular vesicles. An enhanced antigen presentation capacity of dendritic cell for priming of naive T cells was detected in the presence of βγ‐CAT. Collectively, these effects led to strong cytotoxic T lymphocyte responses and antigen‐specific antibody responses. Our findings provide evidence that a vertebrate‐secreted pore‐forming protein can augment antigen presentation by directly modulating cellular endocytic and exocytic pathways, leading to robust activation of adaptive immunity.